LA POÉTICA CLAUSTROFÓBICA DE LOS NO-HOGARES EN REPULSIÓN (ROMAN POLANSKI, 1965) - Ldo. Alberto Román PADILLA DÍAZ (Fonseca, Journal of Communication, 2023)
The link between closed and claustrophobic scenery and the twisted mind of the female main characters and their unbalanced psyches is a constant feature in psychological terror movies. Nevertheless, in Roman Polanski’s films, it becomes an obsession which is commonplace throughout his movies. A type of original style is created based on resettings, dark lightings and other architectural transformations of great interest and some semiology, which we might label claustrophobic poetics. The purpose of this paper is to investigate the significance of the scenographicpsychological device of the French director throughout his second film, Repulsion (1965).